2009
DOI: 10.1016/j.biopsych.2009.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-Releasing Factor-1 Receptor Activation Mediates Nicotine Withdrawal-Induced Deficit in Brain Reward Function and Stress-Induced Relapse

Abstract: Background-Tobacco addiction is a chronic brain disorder that is characterized by a negative affective state upon smoking cessation and relapse after periods of abstinence. Previous research has shown that blockade of CRF receptors with a non-specific CRF 1 /CRF 2 receptor antagonist prevents the deficit in brain reward function associated with nicotine withdrawal and stress-induced reinstatement of extinguished nicotine seeking in rats. The aim of these studies was to investigate the role of CRF 1 and CRF 2 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
127
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(138 citation statements)
references
References 54 publications
9
127
0
Order By: Relevance
“…Additionally, we found that our frustration stress manipulation increases plasma levels of the stress hormone corticosterone (Selye, 1976), suggesting that this manipulation is stressful to rats . These data are in agreement with results from early studies demonstrating that the removal of contingent (extinction) or noncontingent food reward (a frustrative nonreward manipulation; Amsel, 1958) increases plasma corticosterone, suggesting that unexpected reward omission induces a stress-like state (Coe et al, 1983). Finally, Cottone et al (2009) demonstrated that withdrawal from intermittent palatable food access causes withdrawal-like symptoms (decreased motivation to obtain regular food and anxiety) that are reversed by injections of the CRF1 receptor antagonist R121919 (2,5-dimethyl-3-(6-dimethyl-4-methylpyridin-3-yl)-7 dipropylamino pyrazolo[1,5-a]pyrimidine) (Heinrichs et al, 2002).…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Additionally, we found that our frustration stress manipulation increases plasma levels of the stress hormone corticosterone (Selye, 1976), suggesting that this manipulation is stressful to rats . These data are in agreement with results from early studies demonstrating that the removal of contingent (extinction) or noncontingent food reward (a frustrative nonreward manipulation; Amsel, 1958) increases plasma corticosterone, suggesting that unexpected reward omission induces a stress-like state (Coe et al, 1983). Finally, Cottone et al (2009) demonstrated that withdrawal from intermittent palatable food access causes withdrawal-like symptoms (decreased motivation to obtain regular food and anxiety) that are reversed by injections of the CRF1 receptor antagonist R121919 (2,5-dimethyl-3-(6-dimethyl-4-methylpyridin-3-yl)-7 dipropylamino pyrazolo[1,5-a]pyrimidine) (Heinrichs et al, 2002).…”
Section: Introductionsupporting
confidence: 82%
“…On the test day, we assess palatable food intake for 2 h after 15 min exposure to the sight of the food . This "frustrative nonreward" manipulation (Amsel, 1958) or "frustration stress" manipulation, in combination with cycles of food restriction/refeeding, causes "binge-like" palatable food consumption during the first 15 min of the 2 h feeding test Micioni Di Bonaventura et al, 2012). We operationally define "binge eating" in our model as significantly higher palatable food consumption during the 2 h test in the repeated restriction plus frustration stress condition than in the other experimental conditions (see Materials and Methods).…”
Section: Introductionmentioning
confidence: 99%
“…Normalized levels of CRF-R1 and CRF-R2 during withdrawal may be important, given that these receptors are necessary for the expression of the behavioral effects of nicotine withdrawal. 35,36 Future studies are warranted to examine posttranslational changes in neuropeptide receptor levels during withdrawal and the mechanisms by which these changes occur following chronic nicotine exposure.…”
Section: Discussionmentioning
confidence: 99%
“…CRF is required for cocaine seeking induced by stress, but not a cocaine challenge Lee et al, 2003;Lu et al, 2001;Shaham et al, 1998;Wang et al, 2007;but see, Przegaliński et al, 2005). Stressinduced reinstatement following heroin (Shaham et al, 1997), alcohol (Lê et al, 2000), and nicotine (Bruijnzeel et al, 2009) SA has also been reported to be CRF dependent. We extend these findings by showing that i.c.v.…”
Section: Stressor-but Not Cocaine-induced Reinstatement Is Crf Dependentmentioning
confidence: 99%